2014
DOI: 10.4103/2278-9626.126213
|View full text |Cite
|
Sign up to set email alerts
|

Forensic importance of maxillary sinus in gender determination: A morphometric analysis from Western Uttar Pradesh, India

Abstract: A series of furan-EDOT copolymer films, namely, P(Fu-EDOT), P(Fu-EDOT-Fu) and P(EDOT-Fu-EDOT), were electrochemically synthesized from their corresponding monomers and evaluated as active electrode materials for supercapacitor applications by galvanostatic charge-discharge method. The specific capacitance of these copolymers was calculated to be 65, 46 and 75 F g -1 at a current density of 1 A g -1 , respectively. Besides, their energy density were also investigated. Among them, P(EDOT-Fu-EDOT) exhibited highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 27 publications
3
26
1
Order By: Relevance
“…When the skeleton exists completely, sex can be determined with 100% accuracy. The precision rate is 98% in cases of pelvis and cranium, 95% in pelvis and long bones, and 80–90% only with long bones [3, 5]. Gender can be determined by various methodologies such as sexual dimorphism with tooth morphology, pulpal DNA analysis, study of lip prints, palatal rugae, and finger prints and even with radiological techniques by morphometric analysis of paranasal sinuses [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When the skeleton exists completely, sex can be determined with 100% accuracy. The precision rate is 98% in cases of pelvis and cranium, 95% in pelvis and long bones, and 80–90% only with long bones [3, 5]. Gender can be determined by various methodologies such as sexual dimorphism with tooth morphology, pulpal DNA analysis, study of lip prints, palatal rugae, and finger prints and even with radiological techniques by morphometric analysis of paranasal sinuses [1].…”
Section: Discussionmentioning
confidence: 99%
“…By 12-13 years, the sinus floor is in level with the nasal floor, and by 20 years, with the completion of the eruption of the third molars, the pneumatization of the sinus ends and it reaches 5 mm inferior to the nasal floor. Henceforth, subjects included in the present study were above the age of 20 [3, 5]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Szilvassy suggested various shapes of maxillary sinus, that is, triangular, leaf, scapular, and renal shaped. It has been reported that triangular sinuses were the most common in both females and males [7]. It varies greatly in size, shape, and position not only in different individuals but also in different sides of the same individuals.…”
Section: Introductionmentioning
confidence: 99%